Use of Nanotechnology for the Bioremediation of Contaminants: A Review - Vázquez-Núñez, Edgar; Molina-Guerrero, Carlos Eduardo; Peña Castro, Julián Mario; Fernández-Luqueño, Fabián; de la Rosa-Alvarez, Maria G. (Processes, 2020)
Contaminants, organic or inorganic, represent a threat for the environment and human health and in recent years their presence and persistence has increased rapidly. For this reason, several technologies including bioremediation in combination with nanotechnology have been explored to identify more systemic approaches for their removal from environmental matrices. Understanding the interaction between the contaminant, the microorganism, and the nanomaterials (NMs) is of crucial importance since positive and negative effects may be produced. For example, some nanomaterials are stimulants for microorganisms, while others are toxic. Thus, proper selection is of paramount importance. The main objective of this review was to analyze the principles of bioremediation assisted by nanomaterials, nanoparticles (NPs) included, and their interaction with environmental matrices. It also analyzed the response of living organisms employed to remediate the contaminants in the presence of nanomaterials. Besides, we discuss the international regulatory frame applicable to these technologies and how they might contribute to sustainability.
Keywords: Contaminantes; Nanomateriales; Biorremediación